School Based Development Of Scout Teachings - Paulus Rahadi Pawitra; Trinovandhi Setyawan (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2020)
This development aims to produce a product of a scout textbook as’part’of an’effort to’create’a fun and active learning process. This study uses a model of floating (Research and development) from Brog and Gall (in Winarno) includes the following stages: 1. Data collection, 2. Planning, 3. Developing products, 4. Small group testing, 5. Revision of the 1st product , 6. Large group test, 7. Revision of the second product, 8. Field testing, 9. Revision of the 3rd program, 10. Dissemination and implementation. The instruments are interviews and questionnaires. Quantitative and descriptive data analysis techniques "qualitative. The results of the validity of the content experts are 91.67%, (very valid), Indonesian language experts 95% (Very Valid), learning media experts are 95% (very valid), Test "small" group is 94% (very valid) , Big "group" test 94.5% (very valid), and field test of 95% (very valid). In the sense of scout textbooks on the qualification "Very feasible" is used. Making scout textbooks based on science can be used as a supporting medium in improving the quality of learning.